Long‐term resilience of above‐ and belowground ecosystem components among contrasting ecosystems. Issue 7 (1st July 2014) - Wardle, David A.; Jonsson, Micael
Abstract : While several studies have explored how short‐term ecological responses to disturbance vary among ecosystems, experimental studies of how contrasting ecosystems recover from disturbance in the longer term are few. We performed a simple long‐term experiment on each of 30 contrasting forested islands in northern Sweden that vary in size; as size decreases, time since fire increases, soil fertility and ecosystem productivity declines, and plant species diversity increases. We predicted that resilience of understory plant community properties would be greatest on the larger, more productive islands, and that this would be paralleled by greater resilience of soil biotic and abiotic properties. For each island, we applied three disturbance treatments of increasing intensity to the forest understory once in 1998, i.e., light trimming, heavy trimming, and burning; a fourth treatment was an undisturbed control. We measured recovery of the understory vascular plant community annually over the following 14 years, and at that time also assessed recovery of mosses and several belowground variables. Consistent with our predictions, vascular plant whole‐community variables (total cover, species richness, diversity [Shannon's H′ ], and community composition) recovered significantly more slowly on the smaller (least fertile) than the larger islands, but this difference was not substantial, and only noticeable in the most severely disturbed treatment. When an index of resilience was used, we were unable to detect effects of island size on the recovery of any property. We found that mosses and one shrub species ( Empetrum hermaphroditum ) recovered particularly slowly, and the higher abundance of this shrub on small islands was sufficient to explain any slower recovery of whole‐ecosystem variables on those islands. Further, several belowground variables had not fully recovered from the most intense disturbance after 14 yr, and counter to our predictions, the degree of their recovery was never influenced by island size. While several studies have shown large variation among plant communities in their short‐term response (notably resistance) to environmental perturbations, our results reveal that when perturbations are applied equally to highly contrasting ecosystems, differences in resilience among them in the longer term can be relatively minor, regardless of the severity of disturbance.